"Living high-training high and low" is equivalent to "living high-training low" for sea level performance - Stray-Gundersen, J.; Levine, B. D. (Medicine & Science in Sports & Exercise, 1997)
Accomplished distance runners (N = 13) served as Ss. Two groups were formed and trained at sea level for six weeks. Two groups, one live-high/train-low and the other live-high/base-train-high/intense-train-low were formed and experienced their experimental conditions for four weeks. Base-training at altitude was primarily steady-state work while the low-training was more specific (for 5K) interval work. There were no significant differences between the two groups. Both conditions improved 5K time and VO2max. Logistical difficulties were reduced in the base-train-high group. Implication: Living high is a prerequisite for altitude acclimatization effects. However, the proportion of training that is non-specific does not need to be performed at sea level. Only when specific, velocity-important training needs to be performed should training be at sea level to ensure the greatest amount of specific benefit and carry-over to competitive performances. The option demonstrated here makes live-high/train-low a more feasible option for many teams.